Manajemen Sumber Daya Manusia Pada Dinas Pariwisata Kota Manado - Fienny Langi; Efraim Dongalemba; Candra Pomantow (Institut Agama Kristen Negeri Manado, 2021)
ABSTRACT. The quality and presence of human resources plays an important role in developing regional tourism capacity. Manado City has promising prospects to increase competitiveness in the tourism sector, both at the regional and national levels. This study examines and identifies how improving the quality of human resource management can have a significant impact on the quality of regional tourism itself. The method used in this research is descriptive qualitative with a systematic description. The research subject is the State Civil Apparatus of the Manado City Tourism Office. Based on the results of the study, it can be concluded that the success of regional tourism development does not only depend on security and political stability, regional budgets, legal policies, or socialization and promotion, but is also influenced by the carrying capacity and utilization of human resources, especially those engaged in tourism.